If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 7 = 7 + 22 Reorder the terms: 7 + 12x = 7 + 22 Combine like terms: 7 + 22 = 29 7 + 12x = 29 Solving 7 + 12x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 12x = 29 + -7 Combine like terms: 7 + -7 = 0 0 + 12x = 29 + -7 12x = 29 + -7 Combine like terms: 29 + -7 = 22 12x = 22 Divide each side by '12'. x = 1.833333333 Simplifying x = 1.833333333
| F(x)=-x^3-x^2+16x+16 | | (9x-15)/4=2x+3 | | -2/3x=2 | | 2=-2/3x | | 5x+7x=14 | | -2x-24/8 | | 4x+23=14x-27 | | 4x-23=14x-27 | | 6x+y=31.5 | | 5x+1=-3x-15 | | 12x-8y=32 | | y/2-y/6=9 | | y=4/5x-1 | | -0.43p=36 | | 5x^2-x^0=80 | | 8/8.5*X=8 | | y=1/5x+4 | | 2x-1=15+5x | | -6t+g=6 | | -6t+6=6 | | -0.0912+0.96v=-0.168 | | -0.0912+0.96=-0.168 | | 3t+4g=6 | | 3t+2d=52 | | 4x^3+6x^2-2x+9=0 | | 3x-6(2x-10)=159 | | 3t+2d=62.5 | | y=y(600-3y) | | 22x+13=-5-7x | | 8(4x-5)=9(x-6)-5 | | -84-10x=8+24 | | 86x-3x=10x+21 |